2010
DOI: 10.4269/ajtmh.2010.10-0194
|View full text |Cite
|
Sign up to set email alerts
|

Health Workers' Use of Malaria Rapid Diagnostic Tests (RDTs) to Guide Clinical Decision Making in Rural Dispensaries, Tanzania

Abstract: Rapid diagnostic tests (RDTs) were developed as an alternative to microscopy for malaria diagnosis. The RDTs detect malaria parasite antigen(s) in whole blood with high sensitivity and specificity. We assessed health worker malaria treatment practices after the introduction of RDTs in peripheral health facilities without microscopy. From December 2007 to October 2008, we introduced histidine-rich protein II (HRP-2)-based ParaHIT RDTs for routine use in 12 health facilities in Rufiji District, Tanzania. Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 9 publications
1
40
0
Order By: Relevance
“…A pooled meta-analysis using random effects (Fig. 4 ) for the 14 studies [ 7 , 16 18 , 30 , 31 , 33 – 40 ] shows an overall compliance of 83 % (95 % CI 80–86 %); I 2 = 99.9 %, Z = 54.35, p < 0.001. Appropriate malaria treatment based on RDT results (Table 2 ) was as low as 39.7 % in a Zambian study [ 38 ] to as high as 99.9 % in Zanzibar [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…A pooled meta-analysis using random effects (Fig. 4 ) for the 14 studies [ 7 , 16 18 , 30 , 31 , 33 – 40 ] shows an overall compliance of 83 % (95 % CI 80–86 %); I 2 = 99.9 %, Z = 54.35, p < 0.001. Appropriate malaria treatment based on RDT results (Table 2 ) was as low as 39.7 % in a Zambian study [ 38 ] to as high as 99.9 % in Zanzibar [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…11 The results of this study were similar for both children and adults. Although some other studies have come to the opposite conclusion, namely that use of MRDTs does result in use of antimalarial drugs more often in those patients with a positive test result, 12 most published observations are in keeping with the most recent WHO recommendations for using MRDTs (see below).…”
Section: Effect Of Mrdts On Treatment Of Patientsmentioning
confidence: 89%
“…It’s well documented that comprehensive training, periodic refresher courses and regular supervision visits leads to improvement of clinicians’ adherence to the new guidelines for malaria management. In fact, recent studies conducted in Tanzania demonstrated that adherence to new malaria guidelines was enhanced by comprehensive training, education and supervision [ 9 , 37 ]. Another study conducted in Ghana found similar results [ 38 ].…”
Section: Discussionmentioning
confidence: 99%